IMPLEMENTATION OF MARKETING MIX AND PURCHASING DECISIONS OF WINGKO BABAT AND PURCHASE INTENTION(on Wingko Tripe Products "Dua Kelapa Muda") - Kurniawan, Zeki; Setiawan, Budi; Riana, Fitria Dina (Agricultural Socio-Economics Journal, 2024)
The marketing strategy for Wingko Babat Dua Kelapa Muda products needs to be adjusted to market changes based on consumer behavior analysis, to increase sales of the company's products. The aim of this research is to implement the marketing mix and purchasing decisions for Wingko tripe as well as purchase intentions for Wingko Tripe Brand Dua Kelapa Muda products. The method in this research uses a descriptive method with primary data obtained from the results of Likert scale data collection. The results of the descriptive analysis show that the marketing mix in the Product aspect has a value of 3.55 which means high, the Price aspect has a value of 3.43 in the high category, the Place aspect has a value of 3.35 in the high category, the Promotion aspect has a value of 3.18 in the high category moderate, the People aspect has a value of 3.16 in the medium category, the Physical Evidence aspect has a value of 3.39 in the medium category, the Process aspect has a value in the medium category, the Purchase Intention aspect has a value of 3.6 in the high category, and the Purchase Decision aspect has a score of 4.3 in the very high category.